Relationship Between Physical Activity Intensity and Uric Acid Levels in Elderly at Social Welfare Service Unit (UPTD) for Elderly, Kupang - Maing, Agatha Juventia Regina Getrude; Koamesah, Sangguanah Marthen Jacobus; Syahrir, Syahrir; Deo, Dwita Anastasia (Jurnal Biologi Tropis, 2025)
The increasing number of elderly individuals in Indonesia has led to a higher prevalence of degenerative diseases, including hyperuricemia. Elevated uric acid levels are often associated with a sedentary lifestyle and low physical activity. Elderly individuals living in social institutions tend to have uniform activity patterns and limited mobility, which may increase their risk of developing elevated uric acid levels. To analyze the relationship between physical activity intensity and uric acid levels among elderly residents at the Kupang Elderly Social Welfare Technical Implementation Unit (UPTD). This was an analytical study with a cross-sectional design involving 45 elderly participants selected through purposive sampling. The intensity of physical activity was assessed using the Physical Activity Scale for the Elderly (PASE) questionnaire, while uric acid levels were measured using a Glucose, Cholesterol, and Uric Acid (GCU) Meter Device. Data were analyzed using univariate and bivariate analyses with the Spearman’s Rho test at a significance level of p < 0.05. Most respondents were aged 60–69 years, and the majority were female. Most elderly participants had low physical activity levels and elevated uric acid levels. The Spearman’s Rho test showed a significant relationship between physical activity intensity and uric acid levels (p < 0.05). There is a significant relationship between physical activity intensity and uric acid levels among elderly individuals at the Kupang Elderly Social Welfare UPTD. Regular physical activity with appropriate intensity according to individual capacity is important to maintain purine metabolism balance and prevent the risk of hyperuricemia.